Abusive Supervision from an Integrated Self‐Control Perspective. Issue 3 (19th December 2017) - Pundt, Alexander; Schwarzbeck, Katharina
Abstract : We investigate the relationship between supervisors' irritation and follower perceptions of abusive supervision. Based on the integrated self‐control framework, we propose a positive relationship between supervisor irritation and abusive supervision. Moreover, we propose this relationship to be buffered by supervisors' self‐control capacities and by external monitoring of the supervisor by upper management. We tested our hypotheses in a two‐source survey study with 96 supervisor‐follower dyads. Our results show a positive relationship between supervisor irritation and abusive supervision and an interaction between supervisor irritation and supervisor self‐control. The interaction pattern revealed a positive relationship between supervisor irritation and abusive supervision if supervisor self‐control is low. We also found an interaction between supervisor irritation and external monitoring in predicting active but not passive forms of abusive supervision. Our findings underline the role of self‐control processes in explaining abusive supervision.